Dopant, composition and carrier profiling for 3D structures. (May 2017) - Vandervorst, W.; Fleischmann, C.; Bogdanowicz, J.; Franquet, A.; Celano, U.; Paredis, K.; Budrevich, A.
Abstract: With the transition from planar to three-dimensional device architectures, devices such as FinFETs, TFETs and nanowires etc. become omnipresent. This requires the dopant atom positioning relative to the gate edges and contacts with controlled 3D distribution, adequate conformality, appropriate concentrations and activation, all of which are important challenges which need to be resolved since they determine the device performance. Developing an appropriate doping technology for the next technology generation requires a concurrent effort in establishing adequate metrology such that appropriate feedback on process steps and the underlying physics can be generated in a timely manner and with sufficient resolution and accuracy. When assessing performance of such metrology tools and concepts for 3D devices and structures, one needs to address not only the ability to achieve 3D spatial resolution, but also the physical property which is probed, i.e. dopants versus carriers, as well as the complexity of the method used because this impacts on success rate, turn-around time, throughput, automation etc. An evaluation in terms of time to data is as important as the technical capabilities. Although techniques with inherently good 3D resolution (e.g. atom probe tomography) might appear to offer the ideal solution for these applications, routine application is still hampered by localization problems during sample preparation, reconstruction artefacts due to inhomogeneous evaporation and differential laser light absorption, limited sensitivity due to the reduced counting statistics, poor tip yield, small throughput, etc. Hence, complementary analysis using 1D methods like secondary ion mass spectrometry (SIMS) are being explored to provide dopant or composition analysis in 3D structures given its high degree of reproducibility, ease of application and industrial acceptance. Targeting carrier profiling in 3D structures and confined volumes as a complement to atom probe (or SIMS) dopant profiles, has led to the extension of scanning probe microscopy (SPM) methods (which are inherently 2D) toward 3D metrology by exploiting either dedicated test structures or through novel approaches such as Scalpel SPM. The application of these SPM methods for 3D structures and confined volumes has demonstrated that the changing surface/volume ratio in confined devices leads to various phenomena (e.g. dopant deactivation, enhanced diffusion, ..) which are not observed in blanket sample experiments. More emphasis should therefore be placed on the analysis of devices and structures with the relevant dimensions relative to the exploration of blanket experiments. Thus, the metrology concepts addressed in this paper may be very useful for such investigations.